2018
DOI: 10.1016/j.bjid.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk behavior score: a practical approach for assessing risk among men who have sex with men in Brazil

Abstract: HIV/AIDS epidemic is not well controlled, and multiple sexual behavior factors help explain high rates of HIV infection among men who have sex with men (MSM). This article proposes to exam the use of a potential risk behavior score for HIV infection, based on the type and number of sexual partners, and condom use, and their associated factors in a sample of MSM in Brazil. A cross sectional RDS (Respondent Driven Sampling) study was performed among 3738 MSM aged 18+ years old from ten Brazilian cities. The risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 31 publications
1
19
0
5
Order By: Relevance
“…We did not find significant associations between alcohol consumption and the willingness to use and intention to adhere to PrEP among MSM, which is consistent with some previous studies [50]. However, other studies have argued that substance use leads to risky sexual behavior, which in turn affects PrEP use [51,52]. Different types of substances (e.g., alcohol, drugs) might produce different effects on PrEP use [53], and further studies are suggested.…”
Section: Discussionsupporting
confidence: 90%
“…We did not find significant associations between alcohol consumption and the willingness to use and intention to adhere to PrEP among MSM, which is consistent with some previous studies [50]. However, other studies have argued that substance use leads to risky sexual behavior, which in turn affects PrEP use [51,52]. Different types of substances (e.g., alcohol, drugs) might produce different effects on PrEP use [53], and further studies are suggested.…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies conducted in different regions of Brazil showed syphilis prevalence among MSM ranging from 9% to 26.3% emphasizing the need for interventions among this group. [69,13,19,23]…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the earlier the onset of sexual activity, the more frequently participants partook in risk behaviors for syphilis infection. [19] This increased risk could be explained by the fact that youth have difficulties in negotiating condom use with partners in the beginning of their sexual life. Thus, the urgency of having new experiences might lead them to higher risk sexual behaviors and the spontaneity or unplanned sexual intercourse encounters are generally associated with the lack of condom use.…”
Section: Discussionmentioning
confidence: 99%
“…A higher score indicates higher risk components. We used the difference in this composite score between baseline and end of follow up (12 months) as a measure of change in risk components [29], where a positive value indicates an increase in high-risk behavior.…”
Section: Hiv Risk Components Scorementioning
confidence: 99%
“…Composite sets of HIV risk components have been previously used in cohorts of serodiscordant couples in seven African countries [26] and Men who have sex with men in China [27], Kenya [28] and Brazil [29], to generate HIV risk scores. In these studies, a lower risk score was associated with 20 to 85% [26,29] lower HIV incidence. The composite score allowed for more precise predictive capability of risk on HIV incidence, than individual predictors [26].…”
Section: Introductionmentioning
confidence: 99%